Genome-wide identification, evolution, and expression analysis of MLO gene family in melon (Cucumis melo L.) - Zhang, Taifeng; Xu, Nan; Amanullah, Sikandar; Gao, Peng (Frontiers in Plant Science, 2023)
Powdery mildew (PM) is one of the main fungal diseases that appear during the cultivation of the melon fruit crop. Mildew Resistance Locus "O" (MLO) is known as a gene family and has seven conserved transmembrane domains. An induced functional loss of a specific MLO gene could mainly confer PM resistance to melons. However, the genomic structure of MLO genes and its main role in PM resistance still remain unclear in melon. In this study, bioinformatic analysis identified a total of 14 MLO gene family members in the melon genome sequence, and these genes were distributed in an uneven manner on eight chromosomes. The phylogenetic analysis divided the CmMLO genes into five different clades, and gene structural analysis showed that genes in the same clade had similar intron and exon distribution patterns. In addition, by cloning the CmMLO gene sequence in four melon lines, analyzing the CmMLO gene expression pattern after infection, and making microscopic observations of the infection pattern of PM, we concluded that the CmMLO5 (MELO3C012438) gene plays a negative role in regulating PM-resistance in the susceptible melon line (Topmark), and the critical time point for gene function was noticed at 24 and 72 hours after PM infection. The mutational analysis exhibited a single base mutation at 572 bp, which further results in loss of protein function, thus conferring PM resistance in melon. In summary, our research evidence provides a thorough understanding of the CmMLO gene family and demonstrates their potential role in disease resistance, as well as a theoretical foundation for melon disease resistance breeding.